THE INFLUENCE OF ECOLOGICAL FACTORS ON THE REGIONAL DEVELOPMENT OF TOURISM - Bozorov, Elyor Boboqulovich; Latifjonova, Adiba Bobirovna (THE INNOVATION ECONOMY, 2026)
In the context of globalization, a number of ecological problems significantly affect not only the tourism sector but also the growth and development of certain regions within a country. Today, as this sector continues to develop, the level of natural resource use and the state of the environment have become key factors determining the development prospects of regions. Furthermore, in regions facing ecological challenges, tourist attractiveness declines, tourism development slows down, and natural landscapes degrade, which gradually reduces the demand for tourism infrastructure. The tourism sector can develop in areas where conducting economic activities is challenging, for example, in ecologically protected zones. Such development fully aligns with global sustainable development criteria while contributing to the preservation of the country’s cultural heritage, environment, crafts, and other resources. The study highlights the impact of ecological factors in regions on long-term and balanced development, the efficiency of natural resource use, and the role of environmental protection measures in tourism infrastructure.